Bifunctional electrocatalysts for water splitting from a bimetallic (V doped-NixFey) Metal–Organic framework MOF@Graphene oxide composite. (30th December 2022) - Gopi, Sivalingam; Panda, Atanu; Ramu, A.G.; Theerthagiri, Jayaraman; Kim, Hansang; Yun, Kyusik
Abstract: An ongoing challenge still lies in the exploration of proficient electrocatalysts from earth-abundant non-precious metals instead of noble metal-based catalysts for clean hydrogen energy through large-Scale electrochemical water splitting. However, developing a non-precious transition metals based, stable electrocatalyst for cathodic hydrogen evolution reaction (HER) and anodic oxygen evolution reaction (OER) is important challenge for modern energy conversion technology. In this report Vanadium doped bimetallic nickel-iron nanoarray, fabricated by carbon supported architecture through carbonization process for electrochemical water splitting. Three types of catalysts were prepared in different molar ratio of Ni/Fe. The electrocatalytic performance demonstrated that the catalyst with equal mole ratio (0.06:0.06) of Ni/Fe possess high catalytic activity for both OER and HER in alkaline and acidic medium. Besides, our findings revealed that the doping of vanadium could play a strong synergetic effect with Ni/Fe, which provide a small overpotential of 90 mV and 210 mV at 10 mA cm −2 for HER and OER respectively compared to the other two catalyst counterparts. Also, the catalyst with 1:1 (Ni/Fe) molar ratio showed a high current density of 208 mA cm −2 for HER at 0.5 M H2 SO4 and 579 mA cm −2 for OER at 1 M KOH solution, the both current densities are much higher than the other two catalysts (different Ni/Fe ratio). In addition, the presented catalysts showed extremely good durability, reflecting in more than 20 h of consistent Chronoamprometry study at fixed overpotential η = 250 mV without any visible voltage elevation. Similarly, the (Ni/Fe) equal ratio catalyst showed better corrosion potential 0.209 V vs Ag/AgCl and lower current density 0.594 × 10 −12 A cm −2 in high alkaline medium. The V-doping, MOF/GO surface defects are significantly increased the corrosion potential of the V-Nix Fey -MOF/GO electrocatalyst. Besides, the water electrolyzed products were analysed by gas chromatography to get clear insights on the formed H2 and O2 products. Graphical abstract: Image 1 Highlights: V-doped bimetallic nickel-iron nanoarray, fabricated by carbon supported architecture through carbonization. The V-Nix: Fey MOF/GO were characterized by Raman, PXRD, FESEM, TEM and XPS. V–Ni0.06 : Fe0.06 MOF/GO showed lower overpotential of 90 mV and 210 V for HER and OER. The water electrolyzed products were analysed by gas chromatography.